“Shaping Europe’s Digital Future” Through a Change of Perspective: The Necessary Rethinking of the Relationship Between Regulation and Innovation in the EU (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The paper analyzes the EU’s digital regulatory framework and argues that its rapid expansion has generated significant multi-regulatory and multi-level enforcement challenges. Overlapping rules and fragmented authorities undermine legal certainty, increase compliance burdens, and risk discouraging innovation and investment. The paper calls for a recalibration of Europe’s digital governance through a Charter-centred balancing of fundamental rights, clearer coordination among regimes, and the use of adaptive regulatory tools. It proposes a model of multi-level economic constitutionalism that aligns legal coherence, institutional simplification, and material investments, enabling the EU to sustain a competitive, innovation-oriented and rights-compliant digital ecosystem.
Keywords: costituzionalismo digitale; intelligenza artificiale; eccesso di regolamentazione; effetto Bruxelles; sovrapposizione normativa